New Horizons of Process Chemistry : Scalable Reactions and Technologies - Tomioka, Kiyoshi; Shioiri, Takayuki; Sajiki, Hironao (Springer Singapore : Imprint: Springer, 2017)
The methodologies and technologies adaptable to process chemistry are the focus of this unique book, as new catalysts, reactions, and methods for the synthesis of functional materials are dealt with in depth for the first time. Those materials take in pharmaceuticals, agrochemicals, functional materials, chemical raw materials, and other substances in the field of process chemistry including green chemistry. Process chemistry underpins the competitiveness of chemical and pharmaceutical industries, but its stagnation is estimated to cause industrial depression and excessive loss. For that reason, chemists focus on process chemistry consistently so that the development of novel and efficient new reactions and technologies provides an essential stimulus. In addition, this volume describes the important development of selected new synthetic devices for process development and the process design for a larger scale, thus furnishing a valuable source for all who are engaged in process chemistry. .
Keywords: Chemistry.; Pharmacy.; Organic chemistry.; Chemical engineering.; Catalysis.; Agriculture.; elektronické knihy; electronic books